(untitled) (International Journal of Innovative Computing, 2014)
Most of the software applications for children with cerebral palsy (CP) do not focus on learning issues. This paper describes a study of learning issues for children with cerebral palsy and their requirements. The findings are translated into a Learning Software Application Design Model (LSAM), which could be used in developing other types of learning software application for children with CP. Guidelines for designing and developing a learning prototype that are compatible with the limited capabilities of children with CP are planned to ensure they are able to grasp the concepts of a learning software application prototype. The prototype is developed using a game application and also a GlovePie Tool. We present discussion on the learning software application design model that used for designing and developing the game learning application prototype.